In vitro Study of Bifidobacterium lactis BL-99 With Fructooligosaccharide Synbiotics Effected on the Intestinal Microbiota - Zhang, Qi; Zhao, Wen; Zhao, Yuyang; Duan, Sufang; Liu, Wei-Hsien; Zhang, Chao; Sun, Siyuan; Wang, Tingting; Wang, Xin; Hung, Wei-Lian; Wang, Ran (Frontiers in Nutrition, 2022)
Probiotics and prebiotics relieve constipation by altering the composition of the intestinal microbiota. However, their synergistic mechanism of action remains unclear. Herein, an in vitro fermentation model was constructed to examine the synergistic effects of Bifidobacterium lactis BL-99 and fructooligosaccharide (FOS) on the regulation of intestinal microbiota from a population with constipation. The utilization of FOS was promoted by BL-99, and the increase rate being 22.33%. Relative to the BL-99 and the FOS groups, the BL-99_FOS group showed a highly significant increase in acetic acid content (P < 0.01) and a marked decrease in CO2 and H2S contents (P < 0.01) in the fermentation broth. In addition, the BL-99_FOS combination significantly changed the structure of the intestinal microbiota, enhanced the relative abundances of beneficial bacteria that relieved constipation, including Bifidobacterium, Fecalibacterium, Lactobacillus, Subdoligranulum, and Blautia, and decreased those of the harmful bacteria, including Bilophila and Escherichia-Shigella. These findings suggested that BL-99 and FOS synergistically regulated the composition and structure of the intestinal microbiota from the population with constipation and increased acetic acid and decreased CO2 and H2S levels, thereby providing a theoretical basis for the application of synbiotics.